Hommes et femmes devant le psychiatre : hygiène mentale et placement asilaire (Belgique, entre-deux-guerres) - Veerle Massin (Les Cahiers de Framespa)
The purpose of this article is to examine the causes of placement in closed psychiatric institutions in Belgium between the two world wars. Rather than starting from the archives produced by these institutions, we will examine the mental health consultation, where the psychiatrist meets men, women, girls and boys. These consultations, which began in the 1920s, resulted in some cases in hospitalization in a closed psychiatric setting. Why ? This is a unique opportunity to study the practice of the same physician in the same place, with respect to both sexes, in an attempt to gain a better understanding of what it means to be placed in psychiatry at a time when psychiatry is expanding its skills outside the traditional asylar model. What is it that drives these men and women to see a psychiatrist ? What elements does the physician use to advise or encourage placement ? What is the place of patients and their relatives in this procedure : do they have the opportunity to express their willingness to be or not to be placed ? This is a preliminary article to a broader study that aims to identify trends that are essential for understanding the whole.